Performance Evaluation of Centrifugal Refrigeration Compressor Using R1234yf and R1234ze(E) as Drop-In Replacements for R134a Refrigerant - Kexin Yi; Yuanyang Zhao; Guangbin Liu; Qichao Yang; Guoxin Yu; Liansheng Li (Energies, 2022)
With the increasing global requirements for environmental protection, refrigerants with ODP of 0 and low GWP are widely concerned and applied. In this paper, the CFD numerical method simulates the R134a centrifugal compressor directly replaced by R1234yf and R1234ze(E). The results show that at the same compressor rotational speed, using R1234yf to replace R134a directly can obtain a higher cooling capacity, but it reduces COP by about 12.5%; using R1234ze(E) to replace R134a directly reduces the cooling capacity under partial working conditions, the COP is reduced by about 7.0%. When the evaporation temperature, condensation temperature, and cooling capacity are the same, compared with the R134a unit, the COP of the R1234ze(E) unit is reduced by about 5.14%, and it is reduced by about 8.93% for the R1234yf unit. For the R134a centrifugal chiller, the drop-in replacement of R134a with R1234ze(E) can obtain better system performance compared with R1234yf.